Human Data Acquisition through Biometrics using LabVIEW - K Nishanth Rao; N. Vasudheva Reddy (Institute of Advanced Engineering and Science, 2017)
Human Data Acquisition is an innovative work done based on fingerprints of a particular person. Using the fingerprints we can get each and every detail of any individual. Through this, the data acquired can be used in many applications such as Airport Security System, Voting System, and Employee login System, in finding the thieves etc. We in our project have implemented in Voting System. In this we use the components such as MyDAQ which is data acquisition device. The coding here is in done in a Graphical Programming language named LabVIEW where the execution of any program is done in a sequential way or step by step according to the data received.